Protecting study participants in emergency research: is community consultation before trial commencement enough?. Issue 1 (12th July 2017) - Henry, Blair; Perez, Adic; Trpcic, Sandy; Rizoli, Sandro; Nascimento, Barto
Abstract : Background: This article presents the results of a community consultation (CC) process completed in Toronto, Ontario, using a random digit dialling technique, on the attitudes and perceptions of the public toward the use of exception from informed consent when conducting emergency research involving the use of massive blood transfusions. Methods: In 2012, our hospital conducted a CC, using a random digit dialling technique, to elicit the attitudes and perceptions of the public toward the use of an exemption from informed consent for an upcoming clinical trial. A total of 500 participants from high violent crime areas were interviewed as part of this consultation. Results: The response rate for the telephone survey was 54%. Participants indicated a personal acceptance rate of 76%, acceptance of the justification for the exception to consent at 81%, thatthe study would meet the best interest of patients and the community at 81% and that youth (between 15 and 18 years) could be enrolled at 71%. When offered, no participant requested an opt-out wrist band to avoid being enrolled in this study. Discussion: The use of violent crime neighborhoods to locate at risk communities was not effective in identifying the appropriate community of interest for this study. Though only representing a small subpopulation from a large Canadian city, the attitudes noted here is suggestive that Canadians may have a similar level of acceptance as the US based on published studies. However, given the resources needed to undertake this process and that in the end it did not elicit any useful feedback or recommendations for enhancing the safety of participants, the future use of phone surveys as a means of engaging communities should be reconsidered. Level of evidence (Level V): This is a retrospective subanalysis of a CC using a randomized phone dialling technique from a site prior to the start of the Pragmatic Randomized Optimal Platelet and Plasma Ratios Trial. The CC was not designed specifically for research purposes and as such reflect only a case study from a single center. Trial registration number: Pre-result, NCT01545232 .